Repercusión cardiovascular de la infección por el nuevo coronavirus SARS-CoV-2 (COVID-19) - Moreno-Martínez, Francisco L.; Moreno-López, Frank L.; Oroz Moreno, Ricardo (CorSalud, 2020)
Repercusión cardiovascular de la infección por el nuevo coronavirus SARS-CoV-2 (COVID-19)